Cathode catalyst layer and preparation method thereof, membrane electrode and fuel cell

By using a solution of a high boiling point solvent and water combination, combined with low-pressure program temperature control and pressing process, the problem of inhomogeneity of the porous structure of the cathode catalytic layer is solved, and the life of the membrane electrode and the performance of the fuel cell are improved.

CN119601676APending Publication Date: 2025-03-11CHINA AUTOMOTIVE INNOVATION CORP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411661601.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the prior art, there is inhomogeneity in the porous structure of the cathode catalytic layer, resulting in a short film electrode life.

Method used

A high-boiling point solvent and water combination was used as a solution, and a cathode catalytic layer with high uniformity was prepared by low-pressure program temperature-controlled heat treatment and press program hot press treatment.

Benefits of technology

The porous structure uniformity of the cathode catalytic layer is improved, the service life of the membrane electrode is extended, and the performance and durability of the fuel cell are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601676A_ABST
    Figure CN119601676A_ABST
Patent Text Reader

Abstract

The invention discloses a cathode catalyst layer and a preparation method thereof, a membrane electrode and a fuel cell, the cathode catalyst layer is arranged on the cathode side of a proton exchange membrane of the membrane electrode, and the method comprises the following steps: providing a material and a solution; the solution comprises water and a high-boiling-point solvent; the boiling point of the high-boiling-point solvent is higher than that of water; the materials comprise a catalyst and perfluorinated sulfonic acid resin; uniformly mixing the materials and the solution to obtain target slurry; coating the target slurry on the cathode side to obtain an initial cathode catalyst layer; and carrying out heat treatment on the initial cathode catalyst layer to obtain the cathode catalyst layer. According to the method, the high-boiling-point solvent and the water are combined to serve as the solution, and the problem that the porous structure of the cathode catalyst layer is non-uniform due to volatilization of the solution of the target slurry at normal temperature in the coating process is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fuel cells, and in particular to a cathode catalyst layer and a preparation method thereof, a membrane electrode and a fuel cell. Background Art

[0002] The membrane electrode is the heart of the fuel cell. The catalyst-coated proton membrane of the membrane electrode includes an anode catalyst layer, a cathode catalyst layer and a proton exchange membrane. The catalyst-coated proton membrane of the membrane electrode is the reaction site of the fuel cell, realizing the conversion of chemical energy into electrical energy. At present, the porous structure of the cathode catalyst layer is non-uniform, which leads to the problem of short life of the membrane electrode. Summary of the invention

[0003] In view of the above problems, the object of the present invention is to provide a method for preparing a cathode catalyst layer, a cathode catalyst layer, a membrane electrode and a fuel cell that can improve the uniformity of the porous structure of the catalyst layer. The technical solution is as follows:

[0004] In one aspect, a method for preparing a cathode catalyst layer is provided, wherein the cathode catalyst layer is disposed on the cathode side of a proton exchange membrane of a membrane electrode, the method comprising:

[0005] Providing materials and solutions; the solution includes water and a high boiling point solvent; the boiling point of the high boiling point solvent is higher than the boiling point of water; the materials include: a catalyst and a perfluorosulfonic acid resin;

[0006] Mixing the material and the solution uniformly to obtain a target slurry;

[0007] Applying the target slurry on the cathode side to obtain an initial cathode catalyst layer;

[0008] The initial cathode catalyst layer is heat-treated to obtain the cathode catalyst layer.

[0009] In an exemplary embodiment, the high boiling point solvent includes an alcohol organic solvent.

[0010] In an exemplary embodiment, the mass ratio of the water to the high boiling point solvent is 1:(1-3).

[0011] In an exemplary embodiment, the heat treatment is carried out by low-pressure programmed temperature control.

[0012] In an exemplary embodiment, the mixing method includes one of ultrasound, grinding, high-energy ball milling or stirring.

[0013] In an exemplary embodiment, after heat-treating the initial cathode catalyst layer to obtain the cathode catalyst layer, the method further comprises:

[0014] The cathode catalyst layer is subjected to a hot pressing process using a press program.

[0015] In an exemplary embodiment, after applying the target slurry on the cathode side to obtain an initial cathode catalyst layer, the method further includes:

[0016] The initial cathode catalyst layer is heat-treated to obtain a first cathode catalyst layer; the target slurry is applied to the first cathode catalyst layer to obtain a second cathode catalyst layer on the first cathode catalyst layer; the second cathode catalyst layer is subjected to a press program hot pressing treatment to obtain the cathode catalyst layer; the cathode catalyst layer includes the first cathode catalyst layer and the second cathode catalyst layer.

[0017] On the other hand, the present invention further provides a cathode catalyst layer, comprising any cathode catalyst layer prepared by any of the above-mentioned preparation methods.

[0018] On the other hand, the present invention also provides a membrane electrode comprising any one of the above-mentioned cathode catalyst layers.

[0019] On the other hand, the present invention also provides a fuel cell, comprising the above-mentioned membrane electrode.

[0020] The present invention discloses a method for preparing a cathode catalyst layer, which is arranged on the cathode side of a proton exchange membrane of a membrane electrode, and the method comprises: providing materials and solutions; the solution comprises water and a high boiling point solvent; the boiling point of the high boiling point solvent is higher than the boiling point of water; the materials comprise: a catalyst and a perfluorosulfonic acid resin; the materials and the solution are mixed evenly to obtain a target slurry; the target slurry is applied on the cathode side to obtain an initial cathode catalyst layer; the initial cathode catalyst layer is heat-treated to obtain a cathode catalyst layer. The present invention avoids the problem of non-uniformity of the porous structure of the catalyst layer caused by the volatilization of the target slurry solution at room temperature during the coating process by selecting a combination of a high boiling point solvent and water as the solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solution of the present invention, the following briefly introduces the drawings required for use in the embodiments or prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0022] Figure 1 is a flow chart of a method for preparing a cathode catalyst layer provided by an embodiment of the present invention;

[0023] Figure 2 is a comparison diagram of polarization curves of different initial membrane electrodes provided by an embodiment of the present invention;

[0024] Figure 3 It is a comparison diagram of polarization curves of membrane electrodes after different durability provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] The membrane electrode is the heart of the fuel cell. The catalyst-coated proton membrane of the membrane electrode includes an anode catalyst layer, a cathode catalyst layer and a proton exchange membrane. The catalyst-coated proton membrane is the reaction site of the fuel cell, realizing the conversion of chemical energy into electrical energy. The uniformity of the porous structure of the cathode catalyst layer in the membrane electrode seriously affects the water-gas mass transfer management. Its non-uniform and dense porous structure will form local water flooding to hinder the gas from entering the reaction area, forming local starvation and carbon corrosion, affecting the life of the catalyst-coated proton membrane, and thus affecting the durability of the fuel cell stack; the non-uniform loose porous structure will react more violently, locally generating large currents and a large amount of heat, resulting in large differences in the current and temperature distribution of the same catalyst-coated proton membrane, thereby affecting the overall life of the catalyst-coated proton membrane, and then leading to the problem of short membrane electrode life. Therefore, ensuring the uniformity of the porous structure in the cathode catalyst layer is an effective means to ensure battery performance and durability. At present, when preparing the cathode catalyst layer, conventional low-boiling point solvents are usually used as dispersants. During drying, the gas temperature and flow rate are changed, and the temperature is stepped to slowly evaporate the solvent. The low-boiling point solvent will evaporate during the coating process, resulting in an uneven porous structure of the cathode catalyst layer. Alternatively, thermal transfer is used to form a relatively dense porous structure of the cathode catalyst layer. However, the evaporation of the low-boiling point solvent too quickly will still cause uneven porous structure of the cathode catalyst layer.

[0027] Therefore, it is very necessary to develop a new cathode catalyst layer preparation method to improve the uniformity of the porous structure of the catalyst layer.

[0028] The present application provides a method for preparing a cathode catalyst layer, wherein the cathode catalyst layer is disposed on the cathode side of the proton exchange membrane of the membrane electrode. Figure 1 , Figure 1 The present invention is a flow chart of a method for preparing a cathode catalyst layer, wherein the method comprises the following steps:

[0029] Step S1: providing materials and a solution; the solution comprises water and a high boiling point solvent; the boiling point of the high boiling point solvent is higher than the boiling point of water; the materials comprise: a catalyst and a perfluorosulfonic acid resin.

[0030] Specifically, regarding the catalyst, the catalyst can be a Pt / C catalyst or a Pt / Co alloy catalyst. Regarding the high-boiling point solvent, the high-boiling point solvent has a higher boiling point, which leads to a slower volatilization rate. Since the boiling point of the high-boiling point solvent is higher than that of water, in the same environment, the volatilization rate of the solution composed of water and the high-boiling point solvent is slower than that of the conventional low-boiling point solvent used in the prior art. The conventional low-boiling point solvent refers to a solvent with a boiling point lower than that of water.

[0031] Step S2: Mix the material and the solution evenly to obtain a target slurry.

[0032] Specifically, a solution of the high boiling point solvent and water is used as a dispersant for the material, and is evenly mixed with the material to obtain the target slurry.

[0033] Step S3: Apply on the cathode side to obtain an initial cathode catalyst layer.

[0034] During the process of applying the target slurry on the cathode side, since the dispersant in the target slurry is a solution composed of the high-boiling point solvent and water, the amount of volatilization of the dispersant during the process of applying the target slurry on the cathode side at room temperature can be ignored. Therefore, the problem of non-uniformity of the porous structure of the cathode catalyst layer caused by the volatilization of the dispersant during the process of applying the target slurry on the cathode side can be avoided.

[0035] Step S4: heat-treating the initial cathode catalyst layer to obtain a cathode catalyst layer.

[0036] In addition, after the target slurry is applied to the cathode side, during the heat treatment of the initial cathode catalyst layer, the embodiment of the present application controls the conditions of the heat treatment so that the dispersant is released slowly and evenly and orderly, which is beneficial to further improve the uniformity of the porous structure of the cathode catalyst layer formed by the material in the target slurry on the cathode side.

[0037] Specifically, the catalyst, as the main catalyst component of the cathode catalyst layer of the membrane electrode, promotes the electrocatalytic reaction of hydroxides, plays a catalytic role in the process of converting chemical energy into electrical energy, and has the advantages of high selectivity, long service life and good recyclability. There are many types of catalysts, with catalysts with different platinum contents. In specific implementation, a catalyst with a suitable platinum content can be selected according to needs.

[0038] Specifically, the perfluorosulfonic acid resin is mainly used as an important component of the cathode catalyst layer of the membrane electrode, and is also a green solid acid catalyst, which is environmentally friendly, has high catalytic activity, can play an efficient catalytic role, and also has high stability and corrosion resistance, which is beneficial to improving the cycle performance of the battery. There are many types of perfluorosulfonic acid resins, and the present invention does not make specific restrictions on the types of perfluorosulfonic acid resins. In specific implementation, a suitable type of perfluorosulfonic acid resin can be selected according to actual needs.

[0039] In the embodiments of the present application, the high boiling point solvent includes an alcohol organic solvent.

[0040] Specifically, the alcohol organic solvent will not react with the catalyst and the perfluorosulfonic acid resin. In the cathode catalyst layer preparation system of the membrane electrode, it is a stable chemical solvent. The alcohol organic solvent is also a green organic solvent because of its low toxicity and environmental friendliness. The alcohol organic solvent is easy to obtain and cheap. By using the alcohol organic solvent as a solution, the preparation cost of the cathode catalyst layer is reduced. Commonly used high-boiling point alcohol organic solvents with boiling points higher than water, such as ethylene glycol (boiling point of 197°C), n-butanol (boiling point of 117-118°C), and n-octanol (boiling point of 196°C), are specifically selected according to the needs. Suitable alcohol organic solvents are selected, for example, n-butanol, ethylene glycol and water are selected as the solution used in the embodiment of the present application. The alcohol organic solvents of these two combinations are selected to achieve the purpose of regulating the volatilization rate of the solution while maintaining the solubility of the solution to the material, thereby achieving the purpose of regulating the heat treatment time and optimizing the porous structure of the cathode catalyst layer. In the embodiment of the present application, the combination ratio of the various combinations of alcohol organic solvents is not specifically limited, and can be set according to specific experimental requirements.

[0041] In the embodiments of the present application, the mass ratio of water to the high boiling point solvent is 1:(1-3).

[0042] Specifically, the embodiments of the present application take into account that the mass ratio of water and high-boiling-point solvent will not only affect the volatilization rate of the mixed solution of water and high-boiling-point solvent as the dispersant in the target slurry, but also affect the solubility of the material in the dispersant, especially the porosity of the cathode catalyst layer forming a porous structure. Therefore, the embodiments of the present application can dissolve the catalyst in the material and the perfluorosulfonic acid resin in the material by regulating the mass ratio of water and high-boiling-point solvent between 1: (1 to 3), and the porosity of the cathode catalyst layer with a porous structure is higher, thereby improving the catalytic performance of the cathode catalyst layer.

[0043] In the embodiments of the present application, the heat treatment method is a low-pressure programmed temperature control method.

[0044] The low-pressure programmed temperature control refers to a heat treatment process in which the temperature is first increased stepwise and then decreased stepwise at a constant pressure in an environment maintained below atmospheric pressure. Considering that the heat treatment condition exceeding 100°C will accelerate the vitrification of the perfluorosulfonic acid resin in the cathode catalyst layer, its proton transfer capacity is reduced, thereby affecting the catalytic performance of the cathode catalyst layer, and considering that the solution in the present application is a high-boiling point solvent and water, it is necessary to set a pressure parameter below atmospheric pressure so that the high-boiling point solution can be volatilized under a heat treatment condition of less than or equal to 100°C, and avoids the problem that the heat treatment condition exceeding 100°C will accelerate the vitrification of the perfluorosulfonic acid resin in the cathode catalyst layer, resulting in a reduction in its proton transfer capacity, thereby affecting the catalytic performance of the cathode catalyst layer. In the embodiment of the present application, the pressure value is maintained between -60 and -20 KPa, the temperature range is controlled at 30 to 100°C, the temperature is first increased in steps and then decreased in steps, the heating rate is controlled at 5 to 15°C / min, and the heating is stopped when the temperature is decreased and the temperature is automatically decreased to the set temperature value. Each temperature point is kept for 5 to 60 seconds. If the solution is not completely volatilized, the heat treatment is continued under low pressure conditions by first increasing the temperature in steps and then decreasing the temperature in steps. The method for judging whether the solution is completely volatilized can be by weighing and recording the mass of the membrane electrode after cooling to the lowest set temperature value by the heat treatment using the low-pressure program temperature control, and continuing the heat treatment according to the above-mentioned low-pressure program temperature control method, cooling to the lowest set temperature value again, and weighing and recording the mass of the membrane electrode again, until the mass of two consecutive weighings remains unchanged, and it is determined that the solution is completely volatilized.

[0045] In addition, the low-pressure programmed temperature control ensures the slow and frequency release of the solution in the target slurry applied on the cathode side through a step-by-step heating process. More specifically, the slow and frequency release refers to the slow and uniform release of the high-boiling point solution in an orderly manner, thereby further ensuring the uniformity of the porous structure of the cathode catalyst layer by controlling the heat treatment process; and then through a step-by-step cooling process, the stress between the catalyst layer particles is slowly released, thereby avoiding the slow cracking and micro-cracks caused by stress accumulation in the cathode catalyst layer, thereby enhancing the mechanical strength of the cathode catalyst layer. The heat treatment process using low-pressure programmed temperature control can improve the uniformity of the porous structure of the cathode catalyst layer, thereby improving the catalytic performance of the cathode catalyst layer, and by enhancing the mechanical strength of the cathode catalyst layer, the service life of the cathode catalyst layer is extended.

[0046] In the embodiment of the present application, the mixing method includes one of ultrasound, grinding, high-energy ball milling or stirring. Specifically, ultrasound mainly relies on the vibration and cavitation effect generated by ultrasound in liquid. The high-speed vibration and micro jet generated during the propagation of ultrasound in liquid can quickly and evenly mix the material and solution. At the same time, the energy of ultrasound can also accelerate the interaction between the material and the solution, and improve the mixing efficiency; the cavitation effect generated by ultrasound in liquid means that under the action of ultrasound, tiny bubbles formed in the liquid will grow rapidly and collapse instantly under the vibration of ultrasound, thereby forming a strong impact force and shear force, thereby breaking up the particles of the agglomerated material, and achieving the purpose of dispersing the material in the solution. The ultrasound generated by the ultrasonic instrument is uniform, so that the material and solution are mixed by using ultrasound, which has the advantages of uniform mixing, short stirring time, and low energy consumption. This application needs to pay attention when using an ultrasonic instrument for mixing. The water bath temperature during the operation should be room temperature or slightly higher than room temperature as much as possible, and the container containing the target slurry needs to be sealed to avoid volatilization of the solution due to excessively high water bath temperature or the container containing the target slurry being open; after the ultrasonic mixing is completed, the temperature of the target slurry will be higher than room temperature under the action of ultrasound, and it is necessary to cool down slightly before proceeding to the next step. Grinding mainly uses mechanical force to evenly disperse the material in the solution. Usually, a grinder or a mortar can be used. High-energy ball milling is to place the ball milling balls, materials and solutions in a closed container for high-speed movement. The ball milling balls strongly impact the materials and solutions, and can effectively break large particles of the materials into tiny particles, so that the materials are evenly dispersed in the solution, so that the materials and solutions are evenly mixed together. Stirring is also used in the mixing and homogenization process of materials and solutions. Materials and solutions can be mixed together, but compared with high-energy ball milling and grinding, stirring is gentler. Stirring can be done manually with a stirring rod, or with a magnetic stirrer or other types of stirring instruments. When the material particles in this application are small and do not need to be refined, this stirring method can be used to mix the material and solution. The appropriate mixing method can be selected according to actual needs.

[0047] In the embodiment of the present application, after the initial cathode catalyst layer is heat-treated to obtain the cathode catalyst layer, the method further includes:

[0048] The cathode catalyst layer is subjected to hot pressing treatment in a press process.

[0049] After the initial cathode catalyst layer is heat-treated to obtain the cathode catalyst layer; the cathode catalyst layer is subjected to a press program hot pressing treatment. Specifically, the hot pressing treatment is a press program hot pressing treatment. The effect of the press program hot pressing treatment on the catalyst layer is mainly reflected in optimizing the pore structure, increasing the porosity, and improving the diffusion effect of gas and water, thereby improving the performance and stability of the fuel cell. In the embodiment of the present application, the maximum pressure value of the program hot pressing treatment is 0.5~3.0Mpa, the holding time of the maximum pressure value is 10~60s, and the temperature is 120~170℃. Specifically, appropriate hot pressing conditions can optimize the porous structure of the cathode catalyst layer, reduce the mass transfer impedance, and avoid the problem that the non-uniform and dense porous structure of the cathode catalyst layer will form local water flooding and hinder the gas from entering the reaction area. Therefore, through the hot pressing treatment of the press program, the cathode catalyst layer and the proton exchange membrane are in closer contact, the contact resistance is reduced, and the porous structure of the cathode catalyst layer is made denser and uniform, the porous structure of the cathode catalyst layer is optimized, and the porosity of the cathode catalyst layer is increased, thereby improving the diffusion effect of gas and water. The membrane electrode can discharge hydrogen ions and electrons in time when operating at high current density, reduce the carbon corrosion reaction of the membrane electrode, and extend the service life of the membrane electrode, thereby improving the performance of the fuel cell and extending the service life of the fuel cell.

[0050] In the embodiment of the present application, after applying the target slurry on the cathode side to obtain an initial cathode catalyst layer, the method further includes:

[0051] The initial cathode catalyst layer is heat-treated to obtain a first cathode catalyst layer; the target slurry is applied to the first cathode catalyst layer to obtain a second cathode catalyst layer on the first cathode catalyst layer; the second cathode catalyst layer is subjected to a press program hot pressing treatment to obtain a cathode catalyst layer, which includes the first cathode catalyst layer and the second cathode catalyst layer.

[0052] After the initial cathode catalyst layer is heat-treated to obtain the first cathode catalyst layer; the target slurry is then applied on the first cathode catalyst layer to obtain the second cathode catalyst layer on the first cathode catalyst layer; the second cathode catalyst layer is subjected to a press program hot pressing treatment to obtain the cathode catalyst layer, which includes the first cathode catalyst layer and the second cathode catalyst layer. Specifically, when preparing the cathode catalyst layer, the uniformity of the cathode catalyst layer can be optimized by applying the target slurry twice, thereby improving the catalytic performance and stability of the cathode catalyst layer, thereby improving the catalytic performance of the membrane electrode, extending the service life of the membrane electrode, thereby improving the catalytic performance of the fuel cell, and extending the service life of the fuel cell.

[0053] The embodiments of the present application also provide a cathode catalyst layer, including a cathode catalyst layer prepared by any one of the preparation methods provided in the embodiments of the present application.

[0054] The cathode catalyst layer is arranged on the cathode side of the proton exchange membrane of the membrane electrode, and the method comprises: providing materials and solutions; the solution comprises water and a high boiling point solvent, wherein the mass ratio of water to the high boiling point solvent is 1:(1-3), the boiling point of the high boiling point solvent is higher than the boiling point of water, and the high boiling point solvent comprises an alcohol organic solvent; the materials comprise: a catalyst and a perfluorosulfonic acid resin; the materials and the solution are mixed uniformly to obtain a target slurry, wherein the mixing method comprises one of ultrasound, grinding, high-energy ball milling or stirring; the target slurry is applied on the cathode side to obtain an initial cathode catalyst layer; the initial cathode catalyst layer is heat-treated to obtain a cathode catalyst layer, wherein , the heat treatment method is a low-pressure program temperature control method; after the initial cathode catalyst layer is heat-treated to obtain the cathode catalyst layer; the cathode catalyst layer is subjected to a press program hot pressing treatment; the cathode catalyst layer can also be prepared by applying the target slurry twice, illustratively, after the initial cathode catalyst layer is heat-treated to obtain a first cathode catalyst layer; then the target slurry is applied on the first cathode catalyst layer to obtain a second cathode catalyst layer on the first cathode catalyst layer; the second cathode catalyst layer is subjected to a press program hot pressing treatment to obtain a cathode catalyst layer, wherein the cathode catalyst layer includes a first cathode catalyst layer and a second cathode catalyst layer.

[0055] The embodiments of the present application also provide a membrane electrode, comprising any cathode catalyst layer provided in the embodiments of the present application.

[0056] A membrane electrode provided in an embodiment of the present application includes any cathode catalyst layer provided in an embodiment of the present application. The present invention has no special requirements on the preparation method of other parts of the membrane electrode except the cathode catalyst layer, and the conventional membrane electrode preparation method in the field can be adopted. The specific preparation process is well known in the membrane electrode field and will not be elaborated here.

[0057] The embodiment of the present application also provides a fuel cell, including a membrane electrode provided by the embodiment of the present application.

[0058] A fuel cell provided in an embodiment of the present application includes a membrane electrode provided in an embodiment of the present application. The present invention has no special requirements for the fuel cell preparation method, and a conventional fuel cell preparation method in the art can be adopted. The specific preparation process is well known in the fuel cell field and will not be described in detail here.

[0059] Example 1

[0060] This embodiment is used to illustrate a method for preparing a cathode catalyst layer, a cathode catalyst layer, a membrane electrode and a fuel cell of the present invention.

[0061] Prepare a 1:1 system slurry of water and n-butanol: the mass of water is 28g, the mass of n-butanol is 28g, the mass of Pt / C catalyst is 1g, and the mass of perfluorosulfonic acid resin is 2.67g, and the target slurry is obtained after mixing; the target slurry is applied on the cathode side of the proton exchange membrane, the initial cathode catalyst layer is heat-treated to obtain a first catalyst layer, and the target slurry is then applied to the first catalyst layer to obtain a second cathode catalyst layer on the first catalyst layer; the second cathode catalyst layer is subjected to a press program hot pressing treatment to obtain a cathode catalyst layer, wherein the cathode catalyst layer includes a first cathode catalyst layer and a second cathode catalyst layer. The heat treatment is carried out in a low-pressure programmed temperature control mode: the pressure value is controlled between -60 and -20Kpa, and the temperatures are 30°C, 65°C, 90°C, 60°C, and 30°C, respectively, and each temperature point is kept for 30s, wherein the heating rate is 15°C / min, and the heating is stopped when the temperature drops to the set temperature point, so that the solvent is slowly and frequently evaporated, and the mass of the membrane electrode is weighed and recorded after the temperature drops to the lowest set temperature value, and the heat treatment is continued according to the above-mentioned low-pressure programmed temperature control mode, and the mass of the membrane electrode is weighed and recorded again after the temperature drops to the lowest set temperature value again, until the mass of two consecutive weighings remains unchanged, ensuring that the solution is completely evaporated, and the heat treatment is stopped; the hot press program conditions: the maximum pressure value is 0.5Mpa, the pressure increase rate is 10Kpa / s, the temperature is 120°C, and the holding time of the maximum pressure value is 20s, so that the thickness of the cathode catalyst layer of the membrane electrode reaches the set value of 5 microns; the conventional membrane electrode preparation method is adopted for other parts of the membrane electrode to obtain an initial membrane electrode. The initial membrane electrode performance test was carried out under the following conditions: hydrogen and air flow ratio of 1.3:2, hydrogen pressure -20Kpa, air pressure 140Kpa, hydrogen dew point temperature 60℃, battery temperature 80℃, and inlet air temperature 75℃. The initial membrane electrode test data was obtained. 2 When the voltage is 0.576V, the initial membrane electrode is subjected to durability treatment to obtain a durable membrane electrode, wherein the durability treatment conditions include different current density points, different hydrogen pressures and air pressures, different dew point temperatures, different stoichiometric ratios of hydrogen and air, etc.; the performance of the durable membrane electrode is tested, and the performance test conditions of the durable membrane electrode are the same as those of the initial membrane electrode, and the test data of the durable membrane electrode are obtained. At 2000mA / cm 2 When , the voltage is 0.548V.

[0062] Comparative Example 1

[0063] Prepare water and ethanol system slurry: 14g of water, 14g of ethanol, 0.5g of Pt / C catalyst, 1.335g of perfluorosulfonic acid resin, mix to obtain slurry; apply the slurry on the cathode side to obtain an initial cathode catalyst layer; heat treat the initial cathode catalyst layer to obtain a cathode catalyst layer. The heat treatment temperature is 60°C and the air flow rate is 5m 3 / min, until the mass of the membrane electrode remains unchanged within a certain period of time. The same performance test conditions and durability treatment conditions as in Example 1 were maintained to obtain the initial membrane electrode test data. 2 When the voltage is 0.513V, the membrane electrode test data after durability is obtained, among which, at 2000mA / cm 2 When , the voltage is 0.436V.

[0064] Example 2

[0065] Compared with Example 1, the mass of the slurry of the water and n-butanol 1:3 system is 84g; the low-pressure program temperature control mode: the pressure value is controlled between -60 and -20Kpa, the temperatures are 40°C, 70°C, 95°C, 70°C, and 40°C, and each temperature point stays for 60s, wherein the heating rate is 10°C / min; the hot press program pressurization: the maximum pressure value is 3Mpa, the pressure increase rate is 10Kpa / s, the temperature is 140°C, and the holding time of the maximum pressure value is 10s; other conditions remain unchanged; the initial membrane electrode test data is obtained, wherein at 2000mA / cm 2 When the voltage is 0.604V, the membrane electrode test data after durability is obtained, at 2000mA / cm 2 When , the voltage is 0.564V.

[0066] Example 3

[0067] Compared with Example 1, water, n-octanol system slurry: the mass of n-octanol is 28g; low pressure program temperature control mode: the pressure value is controlled between -60 and -20Kpa, the temperature is 35°C, 65°C, 95°C, 65°C, 35°C, each temperature point stays for 50s, and the heating rate is 8°C / min; hot press program pressurization: the maximum pressure value is 2Mpa, the pressure increase rate is 10Kpa / s, the temperature is 160°C, and the holding time of the maximum pressure value is 40s; other conditions remain unchanged; the initial membrane electrode test data is obtained, wherein at 2000mA / cm 2 When the voltage is 0.591V, the membrane electrode test data after durability is obtained, at 2000mA / cm 2 , the voltage is 0.552V.

[0068] Example 4

[0069] Compared with Example 1, water, ethylene glycol system slurry: the mass of ethylene glycol is 28g; low pressure program temperature control mode: the pressure value is controlled between -60 and -20Kpa, the temperature is 30°C, 50°C, 90°C, 50°C, 30°C, each temperature point stays for 60s, and the heating rate is 5°C / min; hot press program pressurization: the maximum pressure value is 2Mpa, the pressure increase rate is 10Kpa / s, the temperature is 160°C, and the holding time of the maximum pressure value is 40s; other conditions remain unchanged; the initial membrane electrode test data is obtained, wherein at 2000mA / cm 2 When the voltage is 0.604V, the membrane electrode test data after durability is obtained, at 2000mA / cm 2 When , the voltage is 0.560V.

[0070] Example 5

[0071] Compared with Example 1, water, ethylene glycol, and n-butanol system slurry: the mass of ethylene glycol is 14g, and the mass of n-butanol is 14g; low-pressure program temperature control mode: the pressure value is controlled between -60 and -20Kpa, and the temperatures are 35°C, 65°C, 95°C, 65°C, and 35°C, respectively, and each temperature point stays for 60s, wherein the heating rate is 6°C / min; hot press program pressurization: the maximum pressure value is 2.5Mpa, the temperature is 160°C, the pressure increase rate is 10Kpa / s, and the holding time of the maximum pressure value is 20s; other conditions remain unchanged; the initial membrane electrode test data is obtained, wherein at 2000mA / cm 2 When the voltage is 0.610V, the membrane electrode test data after durability is obtained, at 2000mA / cm 2 When , the voltage is 0.568V.

[0072] Example 6

[0073] Compared with Example 1, the mass of the water / n-butanol 1:4 system slurry is 112 g; other conditions remain unchanged; the initial membrane electrode test data is obtained, wherein at 2000 mA / cm 2 When the voltage is 0.539V, the membrane electrode test data after durability is obtained, at 2000mA / cm 2 When , the voltage is 0.472V.

[0074] Example 7

[0075] Compared with Example 1, the mass of the slurry of the water and n-butanol system 1:0.5 is 14 g; other conditions remain unchanged; the initial membrane electrode test data is obtained, in which at 2000 mA / cm 2 When the voltage is 0.524V, the membrane electrode test data after durability is obtained, at 2000mA / cm 2When , the voltage is 0.457V.

[0076] Example 8

[0077] Compared with Example 1, the catalyst is a Pt / Co alloy catalyst, and the mass of the Pt / Co alloy catalyst is 1g; other conditions remain unchanged; the initial membrane electrode test data is obtained, wherein at 2000mA / cm 2 When the voltage is 0.628V, the membrane electrode test data after durability is obtained, at 2000mA / cm 2 When , the voltage is 0.585V.

[0078] Comparative Example 2

[0079] Compared with Comparative Example 1, the catalyst is a Pt / Co alloy catalyst, the mass of the Pt / Co alloy catalyst is 1g; other conditions remain unchanged; the initial membrane electrode test data is obtained, wherein at 2000mA / cm 2 When the voltage is 0.549V, the membrane electrode test data after durability is obtained, at 2000mA / cm 2 When , the voltage is 0.466V.

[0080] in, Figure 2 The polarization curves of different initial membrane electrodes obtained from the initial membrane electrode test data in Examples 1 to 4 are compared: at a current density of 2000 mA / cm 2 Under the conditions, the initial membrane electrode voltage of the water / n-butanol 1:1 system was 0.576 V, the initial membrane electrode voltage of the water / n-butanol 1:3 system was 0.604 V, the initial membrane electrode voltage of the water / n-octanol system was 0.591 V, and the initial membrane electrode voltage of the water / ethylene glycol system was 0.604 V, all of which were higher than the initial membrane electrode voltage of the water / ethanol system (0.513 V). Figure 3 The polarization curves of membrane electrodes after different durability are compared: specifically, the polarization curves of membrane electrodes after durability in the water-n-butanol 1:1 system and the water-ethanol system. At a current density of 2000mA / cm 2 Under the condition of 1:1 water / n-butanol, the voltage of the membrane electrode after durability is 112mV higher than that of the membrane electrode after durability in the water / ethanol system, while the voltage of the initial membrane electrode in the water / n-butanol 1:1 system is 63mV higher than that of the initial membrane electrode in the water / ethanol system. It can be seen that the initial membrane electrode in the water / n-butanol 1:1 system has better durability. The initial membrane electrode performance of the water / ethanol system decreased from 0.513V to 0.436V after durability, a decrease of 77mV. The initial membrane electrode performance of the water / n-butanol 1:1 system decreased from 0.576V to 0.548V after durability, a decrease of 28mV. The present invention embodies that the membrane electrode performance prepared by combining a high boiling point solvent with a low pressure temperature control program and a hot press is not only far higher than the conventional membrane electrode performance, but also the durability is greatly improved.

[0081] It can be known from the above technical scheme of the embodiment of the present invention that the present invention discloses a method for preparing a cathode catalyst layer, wherein the cathode catalyst layer is arranged on the cathode side of the proton exchange membrane of the membrane electrode, and the method comprises: providing materials and solutions; the solution comprises water and a high boiling point solvent; the boiling point of the high boiling point solvent is higher than the boiling point of water; the materials comprise: a catalyst and a perfluorosulfonic acid resin; the materials and the solution are mixed evenly to obtain a target slurry; the target slurry is applied on the cathode side to obtain an initial cathode catalyst layer; the initial cathode catalyst layer is heat-treated to obtain a cathode catalyst layer. The present invention avoids the problem of non-uniformity of the porous structure of the cathode catalyst layer caused by the volatilization of the solution of the target slurry at room temperature during the coating process by selecting a combination of a high boiling point solvent and water as the solution, thereby improving the uniformity of the porous structure of the cathode catalyst layer, avoiding carbon corrosion reaction, and extending the service life of the membrane electrode based on the cathode catalyst layer, thereby extending the service life of the fuel cell based on the membrane electrode.

[0082] The above description has fully disclosed the specific embodiments of the present invention. It should be pointed out that any changes made by those skilled in the art to the specific embodiments of the present invention do not deviate from the scope of the claims of the present invention. Accordingly, the scope of the claims of the present invention is not limited to the above specific embodiments.

Claims

1. A method for preparing a cathode catalyst layer, characterized in that: The cathode catalyst layer is arranged on the cathode side of the proton exchange membrane of the membrane electrode, and the method comprises: Providing materials and solutions; the solution includes water and a high boiling point solvent; the boiling point of the high boiling point solvent is higher than the boiling point of water; the materials include a catalyst and a perfluorosulfonic acid resin; Mixing the material and the solution uniformly to obtain a target slurry; Applying the target slurry on the cathode side to obtain an initial cathode catalyst layer; The initial cathode catalyst layer is heat-treated to obtain the cathode catalyst layer.

2. A method according to claim 1, characterized in that The high boiling point solvent includes an alcohol organic solvent.

3. A method according to claim 1, characterized in that The mass ratio of the water to the high boiling point solvent is 1:(1-3).

4. A method according to claim 1, characterized in that The heat treatment method is a low-pressure programmed temperature control method.

5. A method according to claim 1, characterized in that: The mixing method includes one of ultrasound, grinding, high-energy ball milling or stirring.

6. A method according to claim 1, characterized in that: After heat treating the initial cathode catalyst layer to obtain the cathode catalyst layer, the method further comprises: The cathode catalyst layer is subjected to a hot pressing process using a press program.

7. A method according to claim 1, characterized in that After applying the target slurry on the cathode side to obtain an initial cathode catalyst layer, the method further includes: The initial cathode catalyst layer is heat-treated to obtain a first cathode catalyst layer; the target slurry is applied to the first cathode catalyst layer to obtain a second cathode catalyst layer on the first cathode catalyst layer; the second cathode catalyst layer is subjected to a press program hot pressing treatment to obtain the cathode catalyst layer; the cathode catalyst layer includes the first cathode catalyst layer and the second cathode catalyst layer.

8. A cathode catalyst layer, comprising any cathode catalyst layer prepared by the preparation method according to any one of claims 1 to 7.

9. A membrane electrode comprising the cathode catalyst layer according to claim 8.

10. A fuel cell comprising the membrane electrode according to claim 9.

Citation Information

Cited By

  • Fuel cell membrane electrode based on cathode catalyst layer prepressing treatment and preparation method thereof

    CN122025669A